Understanding the influence of ICT on pedagogical practices in the teaching of electronics courses in Nigerian tvet institutions - Abubakar, Bashir (2016)
As information and communication technologies get its way into the educational environment, it may be difficult for the teaching and learning activities especially in TVET institutions to remain unchallenged. However, it is evident from the Literature that JCT application as a pedagogical tool in the Nigerian TVET institutions is not a common practice, it also remain unclear how utilization of ICTs enhances teachers pedagogy. Therefore, this study is interested in what effect these ICTs have on teacher's pedagogy practices especially in the teaching of electronic courses. Using activity theory as a guide, multiple case study was conducted. Five TVET institutions and twenty participants were selected using maximum variation and homogeneous purposive sampling strategies respectively. During the institutions visit, classroom observation was carried out, documents such as a curriculum and teachers lecture materials were reviewed for triangulation purpose. Semi-structured interview was conducted with 20 selected participants as primary data collection method. At data analysis stage, Inductive and deductive methods were used to analyze the data, two strategies of grounded theory as open and axial coding were employed. The coding process was achieved through the use of an inherent feature of NVivo 10. Despite numerous positive influence of ICTs on teacher's pedagogical practices, the crosscases highlighted that ICTs have adverse impact on student ethics. ICTs enable teachers to have greater control over their lesson preparation and delivery, through the use of simulation softwares, teachers try to make abstract concept more concrete to students understanding. It is also evident from the findings that there have been challenges inhibiting the successful use of ICTs as a pedagogical tool in the teaching of electronic courses. These challenges include lack of institutional ICT policy and curricular that focuses on ICTs usage as an educational tool among others. Finally, the study suggested consistent researches to be conducted in this area so that stakeholders would be fully aware of new development and challenges toward the use of ICT as pedagogical tool in the teaching of electronic courses